Evaluation and Management of Blunt Trauma Abdomen: Experience With 132 Cases at Chittagong Medical College Hospital - Rahman, MA Mushfiqur; Farooq, Md Abdullah Al; Bhuiyan, Md Akbar Husain; Sajid, Md Minhajuddin; Chowdhury, Tanvir Kabir; Hossain, Md Shahid (Journal of Chittagong Medical College Teachers' Association, 2013)
Identification and management of serious intra abdominal and associated injuries due to blunt mechanisms are challenging. This study aims to evaluate current approach to manage such patients in a leading teaching hospital of a low income country. Methods: This prospective study was carried out in the departments of General surgery and Paediatric surgery, Chittagong Medical College and Hospital; Chittagong; Bangladesh from July, 2001- June, 2002. Total 132 patients suffering from blunt abdominal trauma (BAT) were evaluated. Results: The majority of the trauma victims aged 30 years and below with male predominance. Road traffic accident (RTA) was the leading cause (57.57%). Sixty eight percent (68%) patients were brought to the hospital within 24 hours of injury. Abdominal pain was the commonest mode of presentation (83.33%). External signs of injury in abdomen were noticed in only 39% patients. The most important abdominal finding was features of peritonitis (generalized muscle guard/ rigidity 56% and localized 42%) and absence of bowel sound (73%). Plain X-ray abdomen (100%) and Ultrasonography (USG) were the principal imaging tool (46.87%). Extra abdominal associated injuries were found in 55% patients. Thirty four patient (26.56%) were managed non-operatively. Ileum injury was maximum (21.87%) and liver was the most frequently injured solid organ (14.06%). Wound infection (23.40%), wound dehiscence (17%) and anastomotic leakage (10.63%) were the complications related with laparotomy. Total 8 patients died (mortality 6.06%). Conclusion: Early detection of abdominal visceral injury by proper clinical evaluation and imaging is the key for successful management. The main danger is on delay, not always to the extent of injury, as most of the blunt abdominal trauma patients are amenable to surgical treatment. JCMCTA 2013 ; 24 (1): 35-40